Influence of the advanced joint path strategies on the energy absorption capacity of Ti-6Al-4V Taylor bar based on additive manufacturing. Issue 2 (1st February 2023) - Bai, Ruqing; Liang, Guan; Naceur, Hakim; Coutellier, Daniel; Zhao, Jinglei; Yi, Jin; Luo, Jun; Wang, Li; Pu, Huayan
Abstract: One of the vital parameters of the additive manufacturing (AM) process is the scanning strategy. In this article, advanced joint path strategies based on irregular hexahedrons instead of conventional regular elements are proposed, and the influences of advanced joint path strategies on the energy absorption capacity of Ti-6Al-4V Taylor bar are investigated. In particular, the thermomechanical results reveal that the zigzag loop path strategy has more influence on deformation than all advanced joint path strategies, among which the zigzag joint path strategy has the maximal effect, and the centrosymmetric joint path strategy has the minimal effect. Meanwhile, through the impact response of the Ti-6Al-4V Taylor bar with AM residual stress (AM RS), the centrosymmetric joint path strategy, which can better uniformly distribute the deformation, can maximize the energy absorption capacity of the structure. HIGHLIGHTS: Advanced joint path strategies based on irregular hexahedrons instead of conventional regular elements are proposed. A fully coupled thermomechanical analysis between the AM process and the transient impact problem. Advanced joint path strategies and the generated RS on the impact response of the final workpieces (parts) are studied. A suitable joint path strategy for the generation of a formed part is identified, which allows a maximal energy absorption capacity.